Badi'uzzaman Said Nursi wa Manhajuhu fi Tahqiq al-Kamal al-Insani - Muhammad Hadi Wannes (Universitas Darussalam Gontor, 2019)
This paper will analyze the methods and basics of Badi’uzzaman Sa’id Nursi to form human perfection. Human perfection has been discussed in various scientific disciplines in Islam; kalam, philosophy, tasawwuf or shari`at fields. This is because human perfection is closely related to happiness in both the ‘shahahadah’ or ‘unseen’ realms. Sa’id Nursi’s strengths were the object of this study because of his expertise in expressing human meaning based on the the Qur`an. The results of this discussion contain several points. First, there are aspects of the method, Bediuzzaman combines aspects of shari’ah and haqiqat, faith, Islam and Ihsan. Second, to achieve perfection, humans must carry out the four maqamat processes; that is, feeling himself weak (‘ajz), infidelity (faqr), affection (as-syafaqah), and always reflecting (tafakkur) on al-Qu`ran and the book of creation. All of these things are in the frame of cleansing the soul from egoism (ananiyyah) and ‘nafs ammarah’. Third, besides that, humans must also function all the inner senses (lathaif) in accordance with the worship that is ordered. An ideal example is the Prophet Muhammad and his companions. Fourth, humans are creatures that emit asmaul Husna the most in their potential. hence, a perfect human is who can live and feel this potential.